Reducing carbon emissions by integrating urban water systems and renewable energy sources at a community scale. (May 2020) - Liu, F.; Tait, S.; Schellart, A.; Mayfield, M.; Boxall, J.
Abstract: This paper presents a novel take on the energy-water nexus; exploring the coupling of renewable generation sources with drinking water distribution and wastewater collection assets that can store and release energy in response to temporal changes in residential heat demand. The paper presents the development of a simulation tool that uniquely integrates energy storage in drinking water reservoirs, heat recovery from sewers with wind turbine(s), solar photovoltaic panel(s) and a non-renewable source. Simulations at the scale of a 1000 household community and hourly intervals were used to find the optimal energy generation mix that minimises the total annual carbon emissions (embedded and operational). Three different locations in the UK were studied. Results show that the integrated idealised system is able to satisfy the heat demand for up to 63% of the time across a year with no carbon emissions, and reduce the annual associated C O 2 by 60% when compared to all heat demand being satisfied by natural gas. This work shows that adopting such an interlinked system at a typical neighbourhood scale could help the UK meet its carbon emission obligations by substantially reducing the 18% of the UK's C O 2 emission (currently estimated to be) related to domestic heat use. Highlights: Integrating water assets with renewable energy sources can considerably reduce supply-demand imbalance. An integrated water asset-renewable energy system can reduce the annual C O 2 emissions from domestic heating by almost 60%. In the UK, such an integrated system can satisfy domestic heat demand with no carbon emissions for 63% of the year.